BRUCELLOSIS-AN UNDER-ESTIMATED CAUSE OF ARTHRALGIA & MUSCULAR PAINS IN GENERAL POPULATION - Diju, Inayat Ullah (Journal of Ayub Medical College Abbottabad, 2009)
Background: Muscular pains, arthralgias and arthritis are among the most common symptoms of the patients attending various OPDs and private clinics every day. While the symptoms could be due to a broad spectrum of the illnesses; the infection with Brucella, often overlooked, is one among such causes. The objective of present study is to determine the extent to which this infection contributes towards the presence of such symptoms, and how important it is to rule out this treatable cause in our society, before labelling and treating these as non-specific aches and pains. Methods: This prospective study was conducted on 280 patients at a registered medical specialist clinic between May 2006 and June 2008. The patients of each gender from age 15 years onwards having the symptoms of chronic muscular pains, backache, and arthralgias etc. were included in the study. The exclusion criteria were clear cut bone and joint diseases, connective tissue and systemic disorders. The patients were subjected to evaluation by history taking that especially looked into their involvement with cattle look-after and also the use of milk and other dairy items. The investigations included agglutination test for Brucella. The positive cases were treated and the results followed for satisfactory or mild responses. Results: Out of 280 cases 55 (19.64%) were suffering from infection with Brucella. The above patients had received non-specific treatment with analgesics or even steroids with no benefit. The young females outnumbered males, and rural cases had more incidence than urban; and there was a slight increase in those cases who handled the cattle at home as compared to those who did not. Conclusion: In absence of a good veterinary care of live stock in societies like that of Pakistan , it becomes important to rule out Brucellosis, before labelling the symptoms of a patient as simple, non specific aches and pains; and therefore depriving the patient of a treatable disease if he had one. Keywords: Brucellosis, Myalgias, Arthralgias, Fever, Dairy, Cattle